Comparison of the Pharmacokinetics and Pharmacodynamics of Single-Dose Tenofovir Vaginal Film and Gel Formulation (FAME 05). (1st February 2018) - Robinson, Jennifer A.; Marzinke, Mark A.; Fuchs, Edward J.; Bakshi, Rahul P.; Spiegel, Hans M. L.; Coleman, Jenell S.; Rohan, Lisa C.; Hendrix, Craig W.
Abstract : Objective: Although preexposure prophylaxis with oral tenofovir (TFV) disoproxil fumarate/emtricitabine reduces HIV acquisition rates, poor adherence to and acceptability of daily vaginal gels have led to development of vaginal film formulations to improve adherence and, potentially, to enable episodic use. Study Design: In this 2-arm, cross-over study of a fast-dissolving tenofovir film (40 mg) compared with a previously studied semisolid tenofovir 1% gel (40 mg), 10 healthy women received a single vaginal dose of each study product. Clinical, pharmacokinetic, and antiviral assessments were performed over 1 week after dose. Results: Nine of 10 participants experienced mild to moderate adverse effects, similar between products, with no severe adverse events or events attributed to study products. TFV concentrations after film dosing exceeded concentrations after gel dosing in plasma between 8 and 24 hours ( P ⩽ 0.02). TFV concentrations in cervicovaginal fluid and both TFV and TFV diphosphate concentrations in cervical tissue homogenates were higher after film dosing (all P values < 0.04). The differences ranged from median (interquartile range) 2.9-fold (1.1, 9.0; midvaginal cervicovaginal fluid) to 4.4-fold (2.9, 7.7; plasma). Neither film nor gel demonstrated reduced cervical tissue biopsy infectivity after ex vivo HIV challenge. Conclusion: Single-dose tenofovir film demonstrated consistently higher concentrations in plasma and cervicovaginal samples when compared with gel during the first day after dosing. Single-dose cervical tissue TFV-diphosphate concentrations at 5 hours exceeded steady-state concentrations previously reported with daily oral Truvada dosing. Tenofovir film may provide an alternative to tenofovir oral and gel formulations. Clinical efficacy remains to be tested.